Aerogel Cherenkov detectors in colliding beam experiments. (5th August 2015) - Danilyuk, A F; Kononov, S A; Kravchenko, E A; Onuchin, A P
Abstract: This review discusses the application of aerogel Cherenkov detectors in colliding beam experiments. Such detectors are used for charged particle identification at velocities at which other methods are ineffective. The paper examines aerogel production technology and how the aerogel optical parameters are measured. Data on threshold Cherenkov counters with direct light collection and on those using wavelength shifters are evaluated. Also presented are data on Ring Image Cherenkov detectors with single and multilayer focusing aerogel radiators.